A corrected p-y curve model for large-diameter pile foundation of offshore wind turbine. (1st April 2023) - Zhang, Xiao-ling; Zhou, Rui; Zhang, Guo-liang; Han, Yan
Abstract: With the development of pile-soil interaction theory, at present the sand p - y model of API specification is adopted to the analysis and calculation of large diameter piles under horizontal static load, but the results of the ultimate soil resistance at different depths is underestimated and the initial foundation reaction modulus is overestimated, thus the calculation results are obtained with large errors. For this problem, a finite element numerical model of pile-soil interaction is established in this study, and the calculation models under horizontal static load with different pile diameters and soil depth are analyzed and the data regression is carried out. A correction coefficient is introduced to consider the size effect of large diameter pile, and the variation law of influence index of different factors is discussed. Finally, a corrected sand p - y curve model for single pile foundation with large diameter more than 2 m is proposed. Compared with the results of model test and field test, the calculation results of ultimate soil resistance and initial foundation reaction modulus from the corrected model is more in accord with the actual situation. Highlights: The existing p-y curve is not suitable to the analysis and calculation of large-diameter piles. The effect factors of ultimate soil resistance and initial reaction modulus are analyzed. The influences of size effect and soil depth are considered in the corrected p-y curve model. The reliability and rationality of the corrected p-y curve model are verified.